Land, cows and bullets: A complex history of cattle ranching and armed conflict in Colombia - Triana Ángel, Natalia; Pazos Cardenas, Mateo; Burkart, Stefan (2025)
Cattle ranching in Colombia has been at the heart of the country’s agricultural economy for centuries, contributing significantly to rural livelihoods and national development. However, the sector has also played a profound role in the country’s armed conflict, where the dynamics of land ownership, power and violence are deeply intertwined.